Sugarcane: an unexpected habitat for black yeasts in Chaetothyriales - Flávia de F. Costa; Rafael S. C. de Souza; Morgana F. Voidaleski; Renata R. Gomes; Guilherme F. Reis; Bruna J. F. de S. Lima; Giovanna Z. Candido; Marlon R. Geraldo; Jade M. B. Soares; Gabriela X. Schneider; Edvaldo da S. Trindade; Israel H. Bini; et al. (IMA Fungus)
Abstract Sugarcane (Saccharum officinarum, Poaceae) is cultivated on a large scale in (sub)tropical regions such as Brazil and has considerable economic value for sugar and biofuel production. The plant is a rich substrate for endo- and epiphytic fungi. Black yeasts in the family Herpotrichiellaceae (Chaetothyriales) are colonizers of human-dominated habitats, particularly those rich in toxins and hydrocarbon pollutants, and may cause severe infections in susceptible human hosts. The present study assessed the diversity of Herpotrichiellaceae associated with sugarcane, using in silico identification and selective isolation. Using metagenomics, we identified 5833 fungal sequences, while 639 black yeast-like isolates were recovered in vitro. In both strategies, the latter fungi were identified as members of the genera Cladophialophora, Exophiala, and Rhinocladiella (Herpotrichiellaceae), Cyphellophora (Cyphellophoraceae), and Knufia (Trichomeriaceae). In addition, we discovered new species of Cladophialophora and Exophiala from sugarcane and its rhizosphere. The first environmental isolation of Cladophialophora bantiana is particularly noteworthy, because this species up to now is exclusively known from the human host where it mostly causes fatal brain disease in otherwise healthy patients.